The Effect of Playdough Games on Children's Creativity in Early Childhood Education - Eka Setiawati (Universitas Sultan Ageng Tirtayasa, 2022)
Education can be interpreted as teaching because education in general always requires instruction. In today's education and learning system, the presence of teachers in the teaching and learning process still plays an important role. The purpose of this study was to identify playdough games as an alternative to developing children’s creativity through playdough games in early childhood education. This study used a quasi-experimental method with a post-test control group using 22 students, a control class of 11 students, and an experimental class 11 students. Data collection techniques in this study using observation and documentation techniques. Check List is done by observing directly to the research location. The documentation technique was used to obtain data about the profile of an early chilhood education in Rangkasbitung, Indonesia, obtain data on the names of students who will be used as research samples, and obtain data on student test scores. Based on the results of this study, we found that role-playing affects children’s creativity in early childhood education, with values significance of 0.021 < 0.05. From the results of observation of the ability creativity of children, it can be concluded that thus the game playing a role, there is an influence on the creativity of children early childhood education. Based on the follow-up of this research suggest that teachers make innovations in learning, both in models, strategies, methods, and techniques and the quality of schools are better again.